EPIDEMIOLOGICAL CORRELATION OF BREAST CANCER WITH CERVICAL CANCER - Kawakeb N A Abdulla; Sahar Jassim Abid; Asmaa Taha M Al- Darraji (Scholar Express Journals, 2022)
Breast and cervical cancers are often regarded as a most dangerous malignancies in terms from both prevalence and death among women globally. Screening test knowledge and experience have an essential role in early diagnosis, resulting in reduced morbidity and death. Objective: To study the proportion of female diagnosed with both cancers in Iraq for the year 2022, their place of residence in the city or the rural area, and associated risk factors such as alcohol and smoking. The results indicated that older women, who lived in the city and who used more alcohol and smoking, were more likely to develop breast and cervical cancer.
Keywords: Breast & cervical cancers; city; rural area; risk factors; Iraq